Synthesis of some new benzoxazine derivatives of biological interest - Verma M.; Singh S.; Singh K.N. (My University, 2025)
The synthesis of a number of biologically important imino-quinazolones has been achieved by the condensation of 3-amino-2-aryl-4-quinazolone and aromatic aldehydes.